Faktor-Faktor Yang Berhubungan Dengan Pola Pengobatan Dalam Mengatasi Diare Di Wilayah Sungai Lulut Rt 4,5,6 Berdasarkan Theory Of Planned Behavior (Tpb) - Gresia, Sola; Melviani, Melviani; Hakim, Ali Rakhman (Innovative: Journal Of Social Science Research, 2024)
Diarrhea conditions where the frequency and consistency of defecation increase are related to a person's intention to engage in behavior which is influenced by a person's attitudes and perceptions of subjective norms related to behavior. The aim of the research is to identify the relationship between community behavior and the theory of planned behavior on diarrhea treatment patterns in the Sungai Lulut area RT 4,5,6. Analytical descriptive quantitative observational research method with a Cross Sectional approach. The results show that attitudes, subjective norms and behavioral control towards diarrhea treatment patterns tend to be positive by 61%, 63% and 57%. Variable analysis between attitudes and diarrhea treatment patterns has a p-value of 0.037, while subjective norms have no relationship with a p-value of 0.662 and behavioral control has no relationship with diarrhea treatment patterns with a p-value of 0.246. Conclusion, there is a relationship between attitudes, but there is no relationship between subjective norms and behavioral control on diarrhea treatment patterns with a significant value of >0.05.